Analysis of Annual Report as an Instrument of Intellectual Capital Reporting: a Case Study of Indian Institute of Science - Anuradha, K. T. (Journal of Information and Knowledge, 2008)
Organizations' ability to collect, process and interpret information and transform information into economic value is becoming more and more important. Organizations have been described as using three types of capital: physical capital such as plant, equipment, stock; financial capital such as cash, investments, receivables; and intellectual capital. Intellectual capital (IC) encompasses intangibles such as patents, intellectual property rights, copyrights and franchises. It also includes intellectual material that has been formalized, captured and leveraged to produce higher valued assets. It represents knowledge transformed to something of value to an organization. Annual reports have been used to investigate the IC reporting practices of business firms, and also to investigate the differences in reporting across firms in different countries. Several such studies have used content analysis as a research technique. Until recently, very few organizations have attempted to measure and assess IC. There are a variety of conceptual frameworks that can be used to classify and record IC. However, all these frameworks concentrate on business firms. In this paper an attempt is made to develop a framework to classify and record IC for academic organizations and also a sample analysis of IC as reported in the annual report is carried out. Indian Institute of Science annual reports are taken as study sample for this purpose. The study reveals that annual reports of academic institutions can be used as an instrument in inquiring intellectual capital reporting because these institutions commonly signal what they perceive as important through the reporting mechanism. Important issues are featured, reported and discussed, whereas less important items are absent or relegated to low profile sections of the report. However, according to this preliminary study it is observed that studies focusing exclusively on annual reports risk capturing an incomplete picture of the amount of reporting organizations are engaging in, and thus an incomplete picture of the practices they are studying. Hence to get a comprehensive view, other official reports and also recorded information publicly available have to be considered. Content analysis can be used as a research method in capturing the data but to get better results this method has to be combined with other data capture methods such as interview and survey methods. In this preliminary analysis, the framework suggested is only partial and this can be further extended to include other units of analysis depending on the purpose of the study. The framework suggested can be used by other organizations and also to carry out comparative study of different organizations.